The American occupation of Japan the origins of the Cold War in Asia - Schaller, Michael (New York Oxford University Press, 1985)
This book provides a novel perspective on the origins of the Cold War in Asia, tracing it all the way back to the occupation of Japan after the Second World War. Schaller argues that the reconstruction of postwar Japan not only shaped the future of that country but the future of U.S. policy throughout postwar Asia, leading up to the controversial interventions in China, Korea, and Vietnam. The author shows how after the war, the United States sought to develop Japan as a stable bulwark against both Soviet expansion and Asian revolution. Schaller depicts the intense contest that raged among Americans, pitting the flamboyant Occupation Commander, General Douglas MacArthur, against virtually all civilian and military planners in Washington, including the president. First hailed as a hero and given nearly free reign to shape Japan's future, MacArthur was ultimately denounced by Truman and his advisors as a "bunko artist" who had wrecked Japan's economy and opened it to Communist influence. In place of MacArthur's ambitious social and economic reforms, the new Occupation program reconcentrated power in the hands of Japans's old elite. The book shows how Communist control of China and North Korea cut Japan off from its historic trading partners and forced officials to focus on developing the rich but unstable Southeast Asian states. Washington feared that economic blackmail alone would pull Japan into the Soviet orbit. Determined to secure Japan--the ultimate "domino"--the United States spurned possible detente with China, extended military aid to the French in Indochina, and finally entered the Korean War.--Publisher description.
The End of the Pacific War -- Remaking Japan, 1945 to 1948 -- Northeast Asia and the Pacific, 1945 to 1947 -- Reinterpeting the Postwar World -- An Aborted Treaty -- The Conservative Response to Liberal Reform -- Setting a New Course -- Regional Economic Integration and the Rise of Southeast Asia -- The Peace Treaty: Trying Again -- Japanese Recovery Prospects in the Wake of China's Revolution -- NSC 48 and the Renewed Debate over Asian Communism -- Containment and Recovery in Japan and Southeast Asia -- A Commitment to Vietnam -- Japan and the Rekindled Crisis with China -- At War in Asia -- Afterward: The Workshop of Asia.
Includes bibliographical references (pages 337-343) and index.
Keywords: United States -- Foreign relations -- Japan; United States -- Foreign relations -- Southeast Asia; United States -- Foreign relations -- 1945-1953.; Southeast Asia -- Foreign relations -- United States; Japan -- Foreign relations -- United States; Japan -- History -- Allied occupation, 1945-1952.; Japan -- Foreign relations -- 1945-.